Algorithm and Theorem on Student Activity Problems: V. Longani, S. Buada, D. Samana - Team, Support (Thai Journal of Mathematics, 2015)
In this paper Student Activity Problems are defined. The problems areabout joint activities among n 2 schools. There are p > n different activity rooms andeach school provide p students to join the activities. In each day, each student has tojoin an activity with a condition that in each room there are n students from n differentschools. It is required that each student participate all p activities in p days and eachhas a chance to work only once with every student from other schools. An algorithm isproposed for such arrangement and a related theorem is also given.